Fruit Band, Rock Band: Perth Pub Rock. Issue 1 (1st January 2018) - Trainer, Adam
Abstract: The performance of popular music in pubs is a long established tradition in Australia and, through various socio-cultural and legislative processes, it became a dominant form of entertainment throughout the 1970s and 1980s. Drawing on interviews with musicians and those working in the music industry in Perth during these decades, this article addresses the specific circumstances that saw rock music come to be performed in suburban hotels in Perth, Western Australia, addressing the tensions and distinctions between rock bands and commercial cover bands. Through a discussion of the relationship between these bands and various aspects of the music infrastructure in Perth, this paper charts the emergence of a distinctive brand of pub rock, known as Oz Rock, most readily associated with the existent pub culture in Australian cities during this time.